Computer generated cartoon face - Chu, Wenjing. (2011)
This project demonstrates the successful development of a Cartoon Face Maker application using MATLAB® as the software platform. The application is an image-processing tool that has the ability to detect a single frontal human face from the photograph and transforms it from portrait image to a cartoon face image.